Konsep I’rab dalam Ilmu Nahwu - Tony Fransisca (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2015)
Nahwu's knowledge as we know it today is laden with various rules and theories is the result of a process which is quite long in the history of Arabic linguistics. Wrong review Nahwu science for example about the concept of I'rab. In things that are often frequently considered as a privilege that makes it difficult then to tryto be avoided by various methods recommended in Ta'līm al-Lughah al-abiArabiyah lī Ghair an-Nāthiqīn bihā, then actually that is the completion of manipulation. That problem will always appear during the core of the problem has not been resolved completely. The concept of I'rab must be straightened out. I've always defined it as taghyîr (change) or taghayyur (change) or atsar (address symptoms Ihab).